Mesin Pakan Otomatis Guna Meningkatkan Produktifitas Ternak Lele di Desa Sumbersari, Jember Jawa Timur - Hery Indria Dwi Puspita; Wazirotus Sakinah; Rudianto Rudianto (Indonesian Journal Publisher, 2022)
Catfish is one of the freshwater fish whose demand is increasing every year, both in the form of fresh fish and processed foods. This increase in demand along with the ease of maintenance has made catfish a cultivated commodity that is widely eyed by fish farmers. One of the important aspects in fish farming is the provision of fish feed, although it is relatively easy, but feed management is needed to increase fish production targets. The fish feeding method mostly uses manual sowing on the surface of the pond. This method has weaknesses in terms of labor requirements and the time required if catfish farmers have many ponds, especially if the breeders forget the schedule for fish feeding. The method of implementing this community service consists of socializing activities, presenting material, directing the steps for making automatic fish feeding tools, tool making practices, tool testing and evaluation. The manufacture of this automatic fish feed tool generally consists of making the body of the tool and the assembly of the timer module components. This activity was attended by 20 people who are members of the SYSGA group in Sumbersari District, a community group engaged in catfish farming. The activity went smoothly, the participants seemed enthusiastic during the activity. Further monitoring is needed to determine the level of effectiveness and efficiency of catfish production by breeders after the use of automatic fish feed equipment.